Mechanical loading and orthobiologic therapies in the treatment of post-traumatic osteoarthritis (PTOA): a comprehensive review - Gardashli, Mahammad; Baron, Max; Huang, Charles; Kaplan, Lee D.; Meng, Zhipeng; Kouroupis, Dimitrios; Best, Thomas M. (Frontiers in Bioengineering and Biotechnology, 2024)
The importance of mechanical loading and its relationship to orthobiologic therapies in the treatment of post-traumatic osteoarthritis (PTOA) is beginning to receive attention. This review explores the current efficacy of orthobiologic interventions, notably platelet-rich plasma (PRP), bone marrow aspirate (BMA), and mesenchymal stem/stromal cells (MSCs), in combating PTOA drawing from a comprehensive review of both preclinical animal models and human clinical studies. This review suggests why mechanical joint loading, such as running, might improve outcomes in PTOA management in conjunction with orthiobiologic administration. Accumulating evidence underscores the influence of mechanical loading on chondrocyte behavior and its pivotal role in PTOA pathogenesis. Dynamic loading has been identified as a key factor for optimal articular cartilage (AC) health and function, offering the potential to slow down or even reverse PTOA progression. We hypothesize that integrating the activation of mechanotransduction pathways with orthobiologic treatment strategies may hold a key to mitigating or even preventing PTOA development. Specific loading patterns incorporating exercise and physical activity for optimal joint health remain to be defined, particularly in the clinical setting following joint trauma.